Identification of older adults with Sarcopenia: comparison of two methods - Hanisah Rosli,; Suzana Shahar,; Manal Badrasawi,; Devinder Kaur Ajit Singh,; Noor Ibrahim Mohamed Sakian, (Penerbit Universiti Kebangsaan Malaysia, 2017)
To compare the ability of methods based on skeletal muscle index (SMI) and another one by the European Working Group on Sarcopenia in Older People (EWGSOP) based on both muscle mass and physical function in identifying older adults with sarcopenia. Anthropometric measurements and physical performance (hand grip strength and gait speed) were performed. In order to determine the value of SMI, body impedance analysis was also carried out. A total of 426 older adults, mostly women (60.8%) with mean age of 68.4 ± 6.2 years participated in this study. Methods based on SMI and EWGSOP identified 50.5% and 32.2% older adults as sarcopenic respectively. Method based on SMI showed a significantly higher percentage of men (70.7%) were sarcopenic as compared to women (37.5%) (p < 0.05). No such difference was noted for EWGSOP method, with 28.7% of men were sarcopenic as compared to women (34.4%). Binary logistic regression indicated that aged 75 years and above (adjusted odds ratio: 3.3, 95% confidence interval: 1.9 – 5.6) and having arthritis (adjusted odds ratio: 2.5, confidence interval: 1.3 – 4.7) to be associated with sarcopenia as assessed using method recommended by EWGSOP. The lower prevalence of sarcopenia by EWGSOP as compared to SMI may be due to the more comprehensive method by EWGSOP. Further research regarding validation of these two screening methods against a gold standard of screening for sarcopenia is needed in order to identify the best method..